2006
DOI: 10.1103/physrevb.73.024424
|View full text |Cite
|
Sign up to set email alerts
|

Temperature- and pressure-induced spin-state transitions inLaCoO3

Abstract: We report the continuous variation of the spin moment of cobalt in LaCoO3 across its temperature and pressure-induced spin transitions evidenced with Kβ emission spectra. The first thermal transition is best described by a transition to an orbitally nondegenerate intermediate spin (S=1) state. In parallel, continuous redistribution of the 3d electrons is also indicated by partial fluorescence yield X-ray absorption spectra. At high pressure, our study confirms that the material becomes low spin between 40 and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
154
3
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 182 publications
(174 citation statements)
references
References 57 publications
14
154
3
3
Order By: Relevance
“…In a recent study on cobaltates, the IADs were found varying linearly with the spin. 40 These observations suggest that the IAD has the potential to extend the quantitative spin momentum determination to general cases.…”
Section: Determination Of the Spin Momentum From Xesmentioning
confidence: 94%
See 1 more Smart Citation
“…In a recent study on cobaltates, the IADs were found varying linearly with the spin. 40 These observations suggest that the IAD has the potential to extend the quantitative spin momentum determination to general cases.…”
Section: Determination Of the Spin Momentum From Xesmentioning
confidence: 94%
“…25,40 Let us note the HS and LS XE spectral functions as h(E) and l(E), respectively, which are normalized to unit area at integration. Using them, the IAD value for the complete spin transition can be given as IAD HL ) ∫|h(E) -l(E)| dE.…”
Section: Determination Of the Spin Momentum From Xesmentioning
confidence: 99%
“…In insulators a small intensity of the Kβ' feature is taken as an indication of a low-spin state and this spectral signature has been widely used to identify transitions from high-to low-spin as a function of pressure [16], temperature [17] or composition [18]. For metallic systems it has been observed that the Kβ' feature is very broad [19].…”
mentioning
confidence: 99%
“…It is well known that applying pressure stabilizes the LS state relative to the HS state owing to its small ionic ra- * dius. 13,14) The ion substitution, the thin-film synthesis, and the pulse-laser irradiation also bring about the spin-state change. [25][26][27][28][29] Magnetic field is a promising tool to control the spin states.…”
mentioning
confidence: 99%